DIFFERENCES IN TEAR SECRETION BEFORE AND AFTER PHACOEMULSIFICATION SURGERY USING SCHIRMER I TESTS - Raditya Pradana Daryosta; Arnila Novitasari Saubig; Maharani Cahyono; Trilaksana Nugroho (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Cataract is a serious problem in the world because it is the biggest cause of blindness in the world. Cataract healing can only be done with operative measures, one of them is phacoemulsification. The phacoemulsification technique is the latest operative technique for cataract healing but both conventional techniques or phacoemulsification techniques can cause a decrease in tear secretion after cataract surgery. The reduction in tear secretion can be evaluated using the Schirmer I test. In this study an analysis of differences in tear secretion before and after phacoemulsification surgery.Aims: Knowing, comparing, and analyzing the differences in tear secretion before and after phacoemulsification surgery using the Schirmer I test.Methods: 22 cataract eyes consisting of 15 patients who will undergo phacoemulsification surgery were collected by consecutive sampling at the Sultan Agung Eye Center, Sultan Agung Hospital, Semarang from August to September 2019, examined using the Schirmer I test. After the data was collected, data analyzed with Wilcoxon rank test.Results: A total of 15 cataract patients consisting of 10 female patients and 5 male patients with a total of 22 eye samples. The average tear secretion before and after phacoemulsification surgery was 12.77 ± 2.74 mm and 11.00 ± 1.95 mm. Data were tested with the Wilcoxon rank test, p = 0,000 (p <0.05) which showed a difference in average tear secretion before and after phacoemulsification.Conclusion: There are differences in tear secretion before and after phacoemulsification surgery.